Respecting autonomy in young people. Issue 1002 (5th May 2009) - Beach, R; Proops, R
Abstract : Paediatricians have a duty to protect the life and health of their patients and to respect their autonomy. Usually, there will be no conflict between these duties. Both children and parents want effective care and agree to the medical interventions that that are most likely to provide it. However, when children refuse or resist such interventions, it may be unclear when the duty to protect trumps the duty to respect. This is because children may have differing levels of autonomy, sometimes making them competent to make medical decisions for themselves and at other times not. Further, there may be conflict between the children and their parents in such circumstances. Children may refuse treatments that parents desire or vice versa. Sometimes paediatricians may agree with the child in the face of legal powers of parental guardianship. At other times they may agree with the parents, facing the prospect of forcing treatment on an unwilling child with potentially devastating psychological consequences. This paper will explore this potential ethical and legal minefield by evaluating some practical clinical cases based on the experiences of the primary author. It provides a range of examples of these different types of conflicts, including especially problematic "hard cases" that concern the withdrawal of life-sustaining treatment and child protection. The goal of the article is not simply to morally and legally outline the boundaries of such tensions in paediatric care. It also provides concrete advice about how they should best be resolved in everyday clinical practice.